ANALISIS STRATEGI GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA SDIT COKROAMINOTO - Nur Maulinda, Meisi; Sukma Nugraha, Widdy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Education has a crucial role in developing students' character and skills, especially in the era of globalization and technological advances. Motivation to learn, as a key factor in educational success, is still a challenge in elementary schools, including at SDIT Cokroaminoto. This research aims to analyze strategies for developing student learning motivation implemented by teachers at SDIT Cokroaminoto. The method used is a qualitative method with a descriptive analytical approach with data collection through observation and interviews with school principals, class teachers and subject teachers. Research finds that various innovative learning methods and the use of technology, such as educational applications, have succeeded in increasing students' motivation and learning skills. Although there are challenges related to intrinsic motivation and parental involvement, support from various parties and training for teachers has proven effective in creating an inspiring learning environment. It is hoped that the results of this research can provide insight for other educational institutions in developing appropriate strategies to increase student learning motivation.